2017
DOI: 10.1002/cyto.a.23169
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of NET formation in vitro and in vivo by flow cytometry

Abstract: Neutrophil extracellular traps (NETs) are extracellular chromatin fibers adorned with antimicrobial proteins, such as myeloperoxidase (MPO), which are extruded from activated neutrophils. NETosis is the metamorphosis of neutrophils with NET formation that follows decondensation of DNA and rupture of the plasma membrane. Although NETs play important roles in innate immunity, excessive formation of NETs can be harmful to the hosts. Until now, various methods for evaluation of NETs have been reported. Although ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 27 publications
4
84
0
1
Order By: Relevance
“…A side by side comparison with the assay by Gavillet et al revealed greater sensitivity in the detection of NETosis with our protocol (Fig. 3B and Supporting Information (21,25). Similar to our findings, percentage of SG + cells correlated with NET area stained using DAPI and observed on fluorescent microscopy (25).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A side by side comparison with the assay by Gavillet et al revealed greater sensitivity in the detection of NETosis with our protocol (Fig. 3B and Supporting Information (21,25). Similar to our findings, percentage of SG + cells correlated with NET area stained using DAPI and observed on fluorescent microscopy (25).…”
Section: Discussionsupporting
confidence: 89%
“…However, the assay by Nel et al can underestimate the earlier phases of NETosis when the NETs are still PMN‐appendant. Additionally, Masuda et al utilized Sytox Green (SG), a plasma membrane‐impermeable DNA dye, to detect PMN‐appendant NET‐DNA . Similar to our findings, percentage of SG + cells correlated with NET area stained using DAPI and observed on fluorescent microscopy .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Flow cytometric assays for direct quantification of cell‐bound NETs on isolated neutrophils has recently been described in a limited number of patients . The purpose of this study was to develop a method of NETs marker quantification for potential routine application using whole blood flow cytometry.…”
Section: Introductionmentioning
confidence: 99%